Visualizing functions and complex numbers for the study of signals and systems - Lau, Yi Hong (Nanyang Technological University, 2023)
This report presents the results of creating a toolbox used to assist students in studying concepts in signal analysis, namely, functions and complex numbers. The toolbox is designed as an application (app), using the programming language MATLAB. The content of the report shall be briefly mentioned. The introduction details the objective and motivations for this project. The main body then introduces relevant mathematical concepts highlighting important takeaways followed by the methods used to design and program the app. Features of the toolbox would then be discussed in length, including description of the user interface (UI) and the documentation of user operation instructions. Finally, the conclusion includes recommendations for future work and insight into the overarching theme of education.